(untitled) (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
This research investigated the trend of textile design graduates venturing into entrepreneurship, exploring the motivating factors and strategies employed by these entrepreneurs. The study adopts survey research design using a questionnaire as the data gathering tool. The population of the study are textile graduates in selected schools in Southwest Nigeria comprising of federal universities, state universities and polytechnics. One hundred and four (104) graduates were sampled using snowball sampling techniques. The data collected were analyzed quantitatively through descriptive analysis using frequency, percentage and mean score. The result of the research reveals that they are increasingly involved in textile entrepreneurship. It was discovered that fashion design is the most subscribed entrepreneurial area by textile design graduates closely followed by Adire production. It was also revealed that textile design graduates engage in entrepreneurial areas outside the textile design field such as banking, real estate and web development among others. It is recommended that tertiary institutions should encourage students to participate in entrepreneurial competitions, both within and outside the institution to enlighten them more about textile entrepreneurship. It is also recommended that tertiary institution should update their curricula to ensure that they have adequate theoretical and practical content to produce graduates well-pre pared for the competitive textile market.